Cost Effectiveness and Flexibility of Reverse Logistics for Consumables and Raw Material: An Empirical Investigation - Bokade, Sanjay Umakant; Raut, D.N. Raut (International Journal of Supply Chain Management, 2013)
The modern supply chain management is witnessing a radical transformation as an effect of competitive strategy. The raw material supplier as well as consumable suppliers often faces the situation of their product return. We conducted a recent survey from the raw material, consumable suppliers and the manufacturing units for examining reverse logistics performance in terms of cost effectiveness and flexibility. This study focuses on finding the relationship between the independent variables and the cost and flexibility as performance indicators of reverse logistics. The result of this study provides a template guideline for designing a cost effective and flexible reverse logistics program.